Designing Math Exercises for MOOCs Courses at Ho Chi Minh City University of Technology and Education - Nguyen, Nguyễn Hồng Nhung; Phan, Phan Phương Dung; Le, Lê Thị Thanh Hải; Hoang, Hoàng Nguyên Lý; Nguyen, Nguyễn Lê Thi; Le, Lê Thị Mai Trang (Journal of Technical Education Science, 2024)
The Covid-19 pandemic has become a strong motive for widely adoptation of online education in the World, especially in the higher education. Online education will become a prevalant educational method in 2025. With a desire of creating an educational ecosystem UTE 4.0, Ho Chi Minh City University of Technology and Education has been creating and implementing about 100 MOOCs courses for students since 2019. This paper presents the method for designing Mathematics exercises on Massive Open Online Courses (MOOCs) on the online training system of Ho Chi Minh City University of Technology and Education (UTEX). Each exercise category has been designed suitable with the MOOCs format, which will ensure the online course to be delivered effectively. For each of the exercise category, we will start with the rationale principles, follow by examples and conclude with key design guidances.